Long-term follow-up of blunt cerebrovascular injuries: Does time heal all wounds?. Issue 6 (December 2016) - Laser, Adriana; Bruns, Brandon R.; Kufera, Joseph A.; Kim, Andrew I.; Feeney, Timothy; Tesoriero, Ronald B.; Lauerman, Margaret H.; Sliker, Clint W.; Scalea, Thomas M.; Stein, Deborah M.
Abstract : BACKGROUND: The short-term natural history of blunt cerebrovascular injuries (BCVIs) has been previously described in the literature, but the purpose of this study was to analyze long-term serial follow-up and lesion progression of BCVI. METHODS: This is a single institution's retrospective review of a prospectively collected database over four years (2009–2013). All patients with a diagnosis of BCVI by computed tomographic (CT) scan were identified, and injuries were graded based on modified Denver scale. Management followed institutional algorithm: initial whole-body contrast-enhanced CT scan, followed by CT angiography at 24 to 72 hours, 5 to 7 days, 4 to 6 weeks, and 3 months after injury. All follow-up imaging, medication management, and clinical outcomes through 6 months following injury were recorded. RESULTS: There were 379 patients with 509 injuries identified. Three hundred eighty-one injuries were diagnosed as BCVI on first CT (Grade 1 injuries, 126; Grade 2 injuries, 116; Grade 3 injuries, 69; and Grade 4 injuries, 70); 100 "indeterminate" on whole-body CT; 28 injuries were found in patients reimaged only for lesions detected in other vessels. Sixty percent were male, mean (SD) age was 46.5 (19.9) years, 65% were white, and 62% were victims of a motor vehicle crash. Most frequently, Grade 1 injuries were resolved at all subsequent time points. Up to 30% of Grade 2 injuries worsened, but nearly 50% improved or resolved. Forty-six percent of injuries originally not detected were subsequently diagnosed as Grade 3 injuries. Greater than 70% of all imaged Grade 3 and Grade 4 injuries remained unchanged at all subsequent time points. CONCLUSIONS: This study revealed that there are many changes in grade throughout the six-month time period, especially the lesions that start out undetectable or indeterminate, which become various grade injuries. Low-grade injuries (Grades 1 and 2) are likely to remain stable and eventually resolve. Higher-grade injuries (Grades 3 and 4) persist, many up to six months. Inpatient treatment with antiplatelet or anticoagulation did not affect BCVI progression. LEVEL OF EVIDENCE: Prognostic study, level III; therapeutic study, level IV. Abstract : Supplemental digital content is available in the text.